Meningkatkan Hasil Belajar Pakat Dan Mandiri Melalui Model Discovery Learning Fase A SDN 173524 Balige - Lusiana Sihaloho (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2023)
Abstract. The purpose of this Classroom Action Research is to determine and measure the increase or not of the improvement or not of grade II students of SDN 173524 Balige, Balige District, Toba Regency, North Sumatra Province with the Discovery Learning Method. The subjects of the study were 6 grade II students of SDN 173524 Balige, consisting of 4 men and 2 women. The object of research is the results of learning and independent students in the study of Catholic Religion and Ethics in the material of teaching module 1